2014
DOI: 10.1186/2049-3258-72-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of antenatal care and iron supplementation during pregnancy in preventing low birth weight in Nepal: comparison of national surveys 2006 and 2011

Abstract: BackgroundLow birth weight (LBW) is a major cause of neonatal deaths in developing countries including Nepal. Its social determinants in Nepal have rarely been identified. This study aimed to identify the factors associated with low birth weight among under-five children comparing data from the Nepal Demographic and Health Surveys (NDHS) of 2006 and 2011.MethodsPooled data from the Nepal Demographic and Health Surveys (NDHS) of 2006 and 2011 were analysed initially and the two survey data were then compared se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
53
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 32 publications
14
53
3
1
Order By: Relevance
“…International Journal of Health Science and Technology, 1 (1) 2019 Fitri Handayani, Herlin Fitriani K also in accordance with the results of research conducted by Vishnu Khana, et. al (2014).…”
supporting
confidence: 86%
“…International Journal of Health Science and Technology, 1 (1) 2019 Fitri Handayani, Herlin Fitriani K also in accordance with the results of research conducted by Vishnu Khana, et. al (2014).…”
supporting
confidence: 86%
“…Mothers who had late (third trimester) initiation of ANC had significantly increased odds of delivering a LBW baby. A study in Nepal has also found a two fold increase in the odds for LBW in women who initiated ANC late or did not attend ANC during their pregnancy (Khanal et al, 2014). In Kenya and Malawi initiation of ANC was noticed in the sixth and seventh months respectively (Pell et al, 2013).…”
Section: Reproductive Factors and Lbwmentioning
confidence: 98%
“…Also the compulsory nature of follow-up appointments discourage attendance (Pell et al, 2013). A study in Nepal to find the factors of LBW noted that, mothers who do not attend antenatal care, have an increased odds of having a LBW infant by more than two times (OR 2.3) (Khanal, Zhao, & Sauer, 2014).…”
Section: Number Of Antenatal Visitsmentioning
confidence: 99%
“…There is also a recent trend in findings suggesting that regular low to moderate exercise reduces the risk of delivering the newborns with either very low or very high birth weight [23], though this potential benefit was not detected in Wiebe et al's 2015 meta-analysis of 79 studies. In terms of maternal nutritional supplementation, evidence suggesting a possible impact on low birth weight was limited for antenatal iron supplementation and mixed for multi-micronutrient supplementation [24][25][26]. Moreover, messages of advice on other topics may potentially have played a role, such as advice on growth monitoring, anxiety reduction, or others.…”
Section: Discussionmentioning
confidence: 99%
“…Basic Group (25) Fetal development (19) Reminders for prenatal visit and hospital delivery (6) Care-Seeking (CS) Group (82) Fetal development (19) Reminders for prenatal visit and hospital delivery (8) Warnings & Recognition of danger signs (45) Reminders for government-subsidized projects (10) Good Household Prenatal Practices (GHPP) Group (91) Fetal development (19) Reminders for prenatal visit and hospital delivery (6) Healthy lifestyle (Nutrition, physical activity, etc.) (37)…”
Section: Group Message Categoriesmentioning
confidence: 99%